Aggressive approach for spontaneous pneumothorax treatment in children with Marfan syndrome? - Zarfati, Angelo; Frediani, Simone; Pardi, Valerio; Aloi, Ivan Pietro; Madafferi, Silvia; Accinni, Antonella; Bertocchini, Arianna; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
Background and objectives Marfan syndrome (MS) is a systemic disease of connective tissues consisting of a variable combination of anomalies. These patients have an increased risk of spontaneous pneumothorax (SP). However, there is a scarcity of pediatric literature on management, and no specific guidelines exist. Our aim was to analyze the management of spontaneous pneumothorax in children and adolescents with Marfan syndrome, comparing syndromic and non-syndromic patients. Methods Retrospective analysis of pediatric patients (18 years) with SP diagnosed at our tertiary pediatric hospital (January 10–June 22), with special emphasis on diagnosis, treatment, and follow-up (FU). Results Sixty-six patients with SP were identified, with nine (13%) having MS. In terms of baseline, there were no significant differences between the groups (age, sex, asthma, symptoms, and side, first-line treatment and hospitalization length). Overall, Marfan patients had significantly more first-line treatment failures requiring additional surgery, as well as more contralateral occurrences and the need for surgery/chest drain during the follow-up. Instead, conservative management resulted in significantly more ipsilateral recurrences and the need for surgery/chest drain in Marfan patients than controls during the follow-up. Conclusions Treatment failure, contralateral occurrence, ipsilateral recurrence, and the need for surgery/chest drain during follow-up make management of patients with Marfan syndrome and spontaneous pneumothorax more difficult. In patients with a diagnosed MS a more aggressive first-line management should be considered, bearing in mind the higher risks of this population.